Strategic planning in University Sports Organizations (member of F.I.S.U) - Σκουλά, Εμμανουέλα (Πανεπιστήμιο Πελοποννήσου, 2010)
The core problem of strategic planning is understanding its multi-faceted character and interrelating different aspects of the strategic planning development. The study’s primary purposes were to (a) determine the extent to which University Sports Organizations, members of International Sports Federation (F.I.S.U.), use strategic planning, (b) identify key factors discouraging strategic planning, c) determine the level of satisfaction in relation to predetermine performance indicators, d) develop a strategic planning process model for implementation by those Organizations, and e) examine relationships between the use of strategic planning and the variables: (1) organizations’ model of governance; (2) percentage of students participating in competitions of the university sports organizations to the total number of students engaged in sport activities in higher education; and (3) the percentage of the organizations’ self-generated revenues raised by University Sport Organizations as opposed to state funds. A questionnaire designed by Kriemadis (1992) has undergone some modification for this study. Factor analysis followed by Cronbach’s reliability analysis, were employed in a pilot attempt to ascertain the multidimensionality of each construct and the internal consistency of the extracted factors. The repeated measures Anova, the chi-square test, the paired sample ttest and the t-test independent samples were used for the data analysis. The level of significance was set at 0.05. All 153 University Sports Organizations were surveyed. The response rate was 53.6%, of which 36.7% were classified as strategic planners and statistical significant differences arose between strategic and non-strategic planners regarding the planning processes. The major factor discouraging planning was insufficient financial resources (71.6%), while the level of satisfaction “to a great extent” did not exceed 70% of the organizations for any factor. A generic strategic planning process model has been developed to overcome the difficulties in formulating and implementing plans. This study may constitute the basis for further research in this area.
Keywords: Στρατηγικός σχεδιασμός; Αθλητισμός; Planning; Sports organizations; Strategy; University athletic departments